Desain dan realisasi alat pengukur kandungan kolesterol dalam darah non-invasive - Indras Marhaendrajaya; Eko Hidayanto; Zaenal Arifin; Heri Sutanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Excess total blood cholesterol can lead to heart vessel disorders, stroke and the most fatal can result in death. While testing the cholesterol levels in the blood at this time still use the invasive technique that the patient's blood is taken by using a syringe. This is one of the obstacles / causes of some patients are reluctant to check blood cholesterol. One of the health technologies to detect blood cholesterol in non-invasive is by utilizing the absorption of near infrared ray (NIR) and laser. The change in the physical properties of the resistance shows the chemical content of different solutions. Preparation of non-invasive blood cholesterol gauge by utilizing oxymeter sensor capable of producing voltage changes in various liquid medium and Atmega 8535 microcontroller as a minimum system in controlling output value in digital data form. The system or equipment to be fabricated in this study is a non-invasive method (without injuring the patient's body while taking blood samples) to determine the blood cholesterol content by utilizing the physical properties of laser absorption or NIR sensors on various blood cholesterol levels. From the research results have been made series of sensor interfaces and serial data communications are displayed digitally. The test results show that the equipment made has shown good performance but still limited its performance test. The results of the research will be developed into a national program of providing cheap, non-invasive portable and movable health test kits. Keywords: Heart Disease, Blood Cholesterol, NIR, Laser, Microcontroller.